Infantile cardiac vascular tumour: from prenatal diagnosis to postnatal treatment. (22nd October 2014) - Lin, Ting-Wei; Wang, Jieh-Neng; Kan, Chung-Dann
Abstract Primary vascular tumour of the heart is rare, especially in neonates and infants. We report a male premature newborn with a right atrial tumour associated with a large amount of pericardial effusion detected by screening foetal echography. Diagnosis of capillary haemangioma was confirmed by histopathological examination after complete surgical resection. Other vascular tumours in the neonates and infants reported in the English literatures are reviewed, and one algorithm for both prenatal and postnatal management is proposed.